Analisis Kebijakan Struktur Modal Berdasarkan Pot dan Tot Persepektif Ekonomi Syariah - Iva Faizah; Gustika Nurmalia (JESI (Jurnal Ekonomi Syariah Indonesia), 2020)
This study aims to look at the capital structure of firms listed on the JII index (Jakarta Islamic Index), whether to the Packing Order Theory, where the Packing Order Theory or POT is the theory of the company's capital structure in which the order of the company's capital structure is derived from 1). Corporate Internal Funds, 2). Debt and 3). Issuance of Shares. Meanwhile, Trade of Theory or TOT is a balancing between debt benefits and the use of debt will give advantage to the company itself in the form of Tax Shield or reduction of corporate tax burden. The object of this research is 13 companies that entered into JII Index during period december 2013 –November 2018 with 39 data that prossed The data were processed by multiple linear regression with the dependent variable in the form of Leverage Ratio proxied by Debt to Equity Ratio (DER) and Independent variable of Profitability and Liquidity Ratio both proxied in sequence with Return on Assets (ROA) and Currency Ratio (CR), which then analyzed with perspective Islamic economics. The result of research shows that the structure of capital of indexed companies in Jakarta Islamic Index is more likely to use the pattern of capital structure policy based on Packing Order Theory, where the proportion of Debt to Equity Ratio or proportion of debt to capital is not more than 50% in half of the listed companies.